A closer look at women who underwent colostomy surgery: a qualitative exploratory-descriptive study - Gisiane de Souza Santos; Sandra Maria Cezar Leal; Mara Ambrosina Vargas (Online Brazilian Journal of Nursing, 2006)
A qualitative exploratory-descriptive study on adult women who had undergone intestinal colostomy surgery at least 2 years before was carried out. The research aimed at looking closer at how these women lived with their condition. The research field was a recognized ambulatory service for colostomy surgery patients in a Public Health Institution in the city of Porto Alegre, Southern Brazil. The group studied was made up of adult women with intestinal ostomy, who had been to the above mentioned institution in the period of January and February 2004 in order to get their devices (colostomy pouch, irrigation system and colostomy plug). The following inclusion criteria were adopted in the study: to be 20 years old or up, to be a female and to have intestinal ostomy. Twelve women, who ranged from 34 to 79 years old, were interviewed. Concerning education, one was illiterate, two had unfinished elementary school, four had completed elementary school, another had unfinished high school, two others had completed high school, and two of them had a college degree. Concerning their occupation, six of them were retired, five were homemakers, and one was both a plastic artist and writer. Thematic analysis was used, including the following categories: lack of knowledge about the surgery, everyday difficulties, sexuality and their own body image, concern with their families, intestinal ostomy as an alternative to stay alive, and hope to stay alive as a means of overcoming difficulties. This kind of study is expected to contribute for the nurse’s planning to look after colostomy surgery female patients, both during the pre-operative care and in the ambulatory and home care, especially to help them overcome difficulties.
Key words: Ostomy. Colostomy. Intestinal neoplasias. Women’s Health. Nursing care.